2013
DOI: 10.3329/bjmb.v5i2.13345
|View full text |Cite
|
Sign up to set email alerts
|

Iron Status in Pre-Eclampsia: A Case-Comparison Study

Abstract: Preeclampsia is one of the most leading causes of maternal mortality in developing countries. Many studies have demonstrated the relation between alteration of iron status and preeclampsia. The aim of the study was to assess the status of iron in preeclampsia. This case control study was conducted in the Department of Biochemistry, Dhaka Medical College, Dhaka from July 2010 to June 2011. A total number of 100 pregnant women in the third trimester of pregnancy attending the Obstetrics & Gynaecology Department … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 8 publications
0
2
0
3
Order By: Relevance
“…There are many hypotheses has been suggested to explain its etiology. Many researchers reported that alteration of iron status is a risk factor for the pathogenesis of preeclampsia (Sultana, et al, 2012;Masti, & Pharm, 2014). Excess iron is postulated as causal factor in the oxidative stress in its radical form, which might be involved in the pathogenesis of preeclampsia (Masti, & Pharm, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…There are many hypotheses has been suggested to explain its etiology. Many researchers reported that alteration of iron status is a risk factor for the pathogenesis of preeclampsia (Sultana, et al, 2012;Masti, & Pharm, 2014). Excess iron is postulated as causal factor in the oxidative stress in its radical form, which might be involved in the pathogenesis of preeclampsia (Masti, & Pharm, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Kadar zat besi bebas dalam jumlah yang berlebihan memiliki toksisitas yang tinggi terhadap sel. 5 Toksisitasnya berasal dari kecenderungannya menghasilkan radikal bebas yang menyebabkan kerusakan sel. Kadar zat besi yang berlebihan juga dikaitkan dengan peningkatan stres oksidatif dan disfungsi endotel, yang merupakan patogenesis utama terjadinya preeklampsia.…”
Section: Diskusi Zat Besi Dan Preeklampsiaunclassified
“…Zat besi dilepaskan dari plasenta iskemik akibat destruksi eritrosit, sehingga memicu proses peroksidasi lipid dan stres oksidatif yang menyebabkan disfungsi sel endotel pada preeklampsia. 6 Mekanisme perbaikan vaskular yang buruk disertai dengan vasospasme akan berkembang menjadi disfungsi endotel.…”
Section: Diskusi Zat Besi Dan Preeklampsiaunclassified
See 1 more Smart Citation
“…2 Pre-eclampsia or eclampsia is decreasing in developed countries, but it is still a major cause of maternal death in developing countries like Bangladesh, where about 16% incidence of preeclampsia was reported. 3 It is due to lack of public awareness, inadequate health education, poor socio-economic condition and less antenatal coverage. It would be better to diagnose preeclampsia before clinical manifestation as prevention or delay in the onset of this disease would have a significant impact on maternal and perinatal outcome.…”
Section: Introductionmentioning
confidence: 99%